Investigating the Nexus Between Energy Transition Reporting Practices and Corporate Efficiency in the European Agri-Food Sector - Serhiy Zabolotnyy (Energies)
The research paper investigates the nexus between energy transition reporting practices and corporate efficiency of listed European companies from the agri-food sector. The study relies on key energy-related and financial indicators and logistic regression analysis conducted on 219 EU business entities publishing their financial and non-financial reports between 2004 and 2023. Based on the distribution of financial metrics in the sample, we assumed that entities reporting data on energy transition, either partially or fully, could achieve higher profitability and simultaneously have lower liquidity than non-reporting companies. The panel data model indicated a strong relationship between the reporting status of a business entity, its revenue, and the time variable, demonstrating that the likelihood of providing information on energy transition was associated with the size of a company and increased systemically over time. However, further regression analysis revealed a lack of a persistent, significant relationship between the key financial indicators and the entities’ energy transition reporting status. Considering the substantial changes in the EU regulatory environment associated with introducing CSRD, we conclude that with increasing legal pressure over time, companies will gradually shift towards standardized industry-related reporting practices, resulting in more consistent and transparent evidence of their energy transition strategies.